Pengenalan Tradisi Budaya Bali melalui Aplikasi Game Explore Bali Berbasis Android - Sanjaya, Dewa Putu Andre; Purnawan, I Ketut Adi; Rusjayanthi, Ni Kadek Dwi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 3 Desember 2016, 2016)
Development of Information Technology is very important for human life, one technology that is currently growing very rapidly in the form of smartphone technology is mainly based on Android. The Android platform has become very popular, the game developers seriously take it. Game is one of the entertainment media, but this time the game can be as one media introduction Cultural Traditions Bali. Game Explore Bali is designed to introduce the Bali Cultural Traditions in seven cities in Bali Province. Traditions introduced in the game consists of Ngerebong (Denpasar), Mekotek (Badung), Okokan (Tabanan), Makepung (Jembrana), Ngedeblag (Gianyar), Megibung, Terteran, Gebug Ende (Karangasem) and Ngocang, Bukakak (Buleleng) through a description and picture information. Based on the analysis by using a questionnaire that tested on 30 children for most of the samples. User knowledge about the Bali Cultural Traditions increased by 74% from the initial percentage of 67% through the information displayed on the Game Explore Bali.
Keywords: Game; Explore; Tradisi; Budaya Bali; Anak-anak